The logic of privacy. (Economist, 2007)
The article discusses the use of a philosophical theory called contextual integrity to study the privacy of personal information and privacy invasion. Computer scientist John Mitchell is leading the study. Contextual integrity, developed by Helen Nissenbaum, acknowledges that people do not require complete privacy. The researchers are working to transform the formal expressions of contextual integrity into computer programs through linear temporal logic to study questions of privacy.